The irresistible transistor. - Goldstein, H.
Looks back to the Raytheon CK722, the first transistor sold to the general public, and presents a description of a maintained collection of thousands of early transistor specimens, including dozens of CK722s. The subject of this article maintains a virtual Transistor Museum on the Web.
Keywords: Raytheon CK722.; Maintained collection; Transistor specimens; Virtual Transistor Museum